Exploring membranous NECTIN-4 expression patterns and enfortumab vedotin response in prostate cancer - Weiten, Richard; Bernhardt, Marit; Niemann, Max; Kristiansen, Glen; Grünwald, Viktor; Ritter, Manuel; Hölzel, Michael; Eckstein, Markus; Alajati, Abdullah; Klümper, Niklas; Krausewitz, Philipp (Journal of Cellular and Molecular Medicine, 2024)
Antibody-drug conjugates (ADCs) represent a novel type of targeted cancer therapy combining the specificity of monoclonal antibodies with the cytotoxicity of conventional chemotherapy. Recently, ADCs have demonstrated practice-changing efficacy across diverse solid cancers. The anti-NECTIN-4 ADC enfortumab vedotin (EV) has just been approved for patients with urothelial cancer and is currently under investigation for patients with castration-resistant prostate cancer (CRPC e.g. Phase II ENCORE trial). Our objective was to evaluate the efficacy of EV in established prostate cancer (PCa) cell lines and to examine the membranous NECTIN-4 expression in primary tumours (PRIM) and distant metastases (MET). NECTIN-4 was heterogeneously expressed in the panel of PCa cell lines. EV led to growth inhibition in NECTIN-4 expressing PCa cells (22Rv1 and LNCaP), whereas the NECTIN-4-negative PC-3 cells were significantly less responsive to EV, emphasizing the dependence of EV response on its target expression. Immunohistochemical staining revealed moderate membranous NECTIN-4 expression only in a small subgroup of CRPC patients with lung and peritoneal MET [n = 3/22 with H-score ≥100, median H-score 140 (IQR 130–150)], while 100% of PRIM (n = 48/48) and 86.4% of common MET sites (n = 19/22), including lymph node, bone and liver MET, were NECTIN-4 negative. In summary, EV may be effective in NECTIN-4-positive PCa. However, our findings demonstrate that the tumoural NECTIN-4 expression is predominantly low in metastatic PCa, which suggests that EV may only be effective in a biomarker-stratified subgroup.
CRIS-Team Scopus Importer:2024-08-09
Keywords: antibody-drug conjugates; enfortumab vedotin; mCRPC; NECTIN-4; prostate cancer